2012
DOI: 10.3390/md10112608
|View full text |Cite
|
Sign up to set email alerts
|

seco-Briarellinone and Briarellin S, Two New Eunicellin-Based Diterpenoids from the Panamanian Octocoral Briareum asbestinum

Abstract: Two new eunicellin-based diterpenes, seco-briarellinone (1) and briarellin S (2), and a known seco-asbestinin (3) have been isolated from the methanolic extract of the common octocoral Briareum asbestinum collected in Bocas del Toro, Caribbean of Panama. The structures and relative stereochemistry of the compounds were defined using extensive spectroscopic analysis including 1D, 2D-nuclear magnetic resonance (NMR) and high-resolution mass spectrometry (HRMS). compounds 1 and 2 displayed anti-inflammatory prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…Seven degrees of unsaturation were calculated from the molecular formula: three accounted for carbonyls of ester and ketone and one double bond, hence compound 1 possesses four rings. Detailed analysis of 1 H and 13 C NMR data indicated the structure of briarellin T (1) was similar to briarellin S, previously reported from our group [10]. 13 C-NMR and DEPT spectra showed the presence of one ketone (δ C 214.3), one ester carbonyl (δ C 173.5), one double bond (δ C 124.8, 129.9) and five methyl groups (δ C 11.4, 19.6, 18.8, 22.6, 14.0) (Table 1).…”
Section: Isolation and Characterization Of Diterpenessupporting
confidence: 83%
See 3 more Smart Citations
“…Seven degrees of unsaturation were calculated from the molecular formula: three accounted for carbonyls of ester and ketone and one double bond, hence compound 1 possesses four rings. Detailed analysis of 1 H and 13 C NMR data indicated the structure of briarellin T (1) was similar to briarellin S, previously reported from our group [10]. 13 C-NMR and DEPT spectra showed the presence of one ketone (δ C 214.3), one ester carbonyl (δ C 173.5), one double bond (δ C 124.8, 129.9) and five methyl groups (δ C 11.4, 19.6, 18.8, 22.6, 14.0) (Table 1).…”
Section: Isolation and Characterization Of Diterpenessupporting
confidence: 83%
“…Briarellins and asbestinins are biologically active marine natural products with great pharmacological potential due to their variety of properties, including antimicrobial, antiviral, antimalarial, and cytotoxic activities [9,14]. Moreover, a previous study from our group has reported that briarellin S reduced NO levels in LPS-stimulated primary murine macrophages [10]. However, there is no more evidence that reports the anti-inflammatory activity of these marine compounds.…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Table 2, and in contrast to the 20 marine compounds ( 115 – 134 ) with described anti-inflammatory mechanisms of action, for marine compounds ( 135 – 157 ), only anti-inflammatory activity, namely IC 50 , was reported, but the molecular mechanism of action remained undetermined: A. polyacanthus steroids ( 135 , 136 ) [137]; barettin ( 137 ) [138]; briarenolide F ( 138 ) [139]; diketopiperazine ( 139 ) [140]; 6- epi -cladieunicellin F ( 140 ) [141]; crassarosteroside A ( 141 ) [142]; cystodione A ( 142 ) [143]; densanins A and B ( 143 , 144 ) [144]; dissesterol ( 145 ) [145]; echinohalimane A ( 146 ) [146]; eunicidiol ( 147 ) [147]; flexibilisolide C ( 148 ) [148]; flexibilisquinone ( 149 ) [149]; lobocrassin F ( 150 ) [150]; perthamide J ( 151 ) [151]; pseudoalteromone A ( 152 ) [152]; sarcocrassocolide M ( 153 ) [153]; sclerosteroids K and M ( 154 , 155 ) [154]; seco-briarellinone ( 156 ) [155]; and sinularioside ( 157 ) [156]. …”
Section: Marine Compounds With Antidiabetic and Anti-inflammatory mentioning
confidence: 99%